Hydrocarbon forming condition and accumulation model of the buried-hill reservoir in the Beier sag, Hailar Basin - Yixuan Ran (Unconventional Resources)
The Hailar basin is an important petroliferous basin in Northeast China, the buried-hill is not only the primary oil productive formation, but also an important unconventional resource and risk exploration target in Hailar Basin. However, relatively few studies have investigated the characteristic and forming condition of the buried-hill reservoir. This article describes the genesis and characteristic of different kinds of buried-hill, discusses the hydrocarbon forming condition, such as source rock, favorable reservoir, transport channel, hydrocarbon supply windows, cap rock, and their relationship with the buried-hill reservoir, and concludes by discussing the accumulation model. The result is that, the ranges of TOC and S1+S2 is 0.54–3.34 % and 4.34–18.13 mg/g, with an average value of 1.93 % and 6.84 mg/g, respectively. The Ro ranges from 1.02 % to 1.65 %, indicate the source rock in Nantun Formation is organic rich and thermally mature for hydrocarbon generation. The balanced profile recovery and seismic interpretation demonstrate that there are three kinds of buried-hill, named Pre-formed buried-hill, Syn-formed buried-hill and Post-formed buried-hill. The buried-hill can be divided into five layers, they are Fully weathered clay layer, Highly weathered fracture layer, Medium weathering pore layer, Weakly weathered compact layer and Inside fractured layer, from the top to bottom. The favorable reservoir are concentrate in the Medium weathering pore layer and Inside fractured layer.The results indicate that the oil-bearing buried-hill is controlled by the union of different kinds of hydrocarbon forming condition. They are all nearby the oil-generating depressions in Beixi sub-sag and Beizhong sub-sag. The III-type faults are opened during the main accumulation period, which is the most important transport channel. The hydrocarbon supply windows determine the abundance of the oil reservoir. The Nantun Formation is the advantage steal rock and determine the distribution of oil reservoirs. We recognize two kinds of accumulation model, named “inside bedrock oil reservoir in the Post-formed buried-hill” and “weathering crust oil reservoir in the Syn-formed buried-hill”, and select the Huoermoduo buried-hill, Sudeerte buried-hill and Beizhong buried-hill as the favorable exploration target. The hydrocarbon in Huoermoduo buried-hill is concentrate in the inside bedrock reservoir, while the oil in Sudeerte buried-hill and Beizhong buried-hill are found in the weathering crust reservoir. The forming condition and pattern are different from each other, which is the main reason for the variation distribution of inside bedrock oil reservoir and weathering crust oil reservoir.